Why Starting Writing Is So Difficult? An Analysis On Students’ Experiences In Writing Narrative Text - Delawati Hida; Kartin Lihawa; Muzdalifah Mahmud (Journal of Language Education (JoLE), 2025)
This research was conducted based on the problem, namely second semester students in the English Education Program FSB UNG face the problem of lack of knowledge in composing narrative texts, especially strategies for getting ideas and organizing them into paragraphs. This condition makes most students reluctant to learn to write. There are complicated rules in writing that cannot be ignored, when students write something, they must pay more attention to spelling, punctuation, diction, grammar, the purpose of their writing, and their own writing ideas. In addition, they are confused about how to start writing ideas into a good narrative text. This study collected qualitative data using observation techniques, narrative writing tests, and interviews. The results are; first, students have difficulty organizing ideas in narrative writing. Second; lack of vocabulary, which makes students write sentences that are less communicative. Finally; students are confused about the correctness of the grammar they compose. Based on the results of the analysis, the researcher concluded that there are three reasons that cause students to have difficulty in starting to write. First, organizing ideas, when students are able to express what they want to write but have difficulty putting it into written form. Second, a lack of vocabulary leads students to write less communicative sentences. Finally, due to a lack of grammatical accuracy, students are confused about their writing. Previous research has found similar student difficulties with vocabulary, grammar, and linguistics, including research by Marzona et al. (2019), Nandha et al. (2022), and Fadilah et al. (2024). All of these issues make it difficult for students to begin writing.